Prescribed Finite-Time Consensus Tracking for Multiagent Systems With Nonholonomic Chained-Form Dynamics - Ning, Boda; Han, Qing-Long (IEEE transactions on automatic control, 2019)
This paper deals with the consensus tracking problem for a multiagent system with nonholonomic chained-form dynamics. A new distributed observer is first proposed for each follower to estimate the leader state and the leader input in a prescribed finite-time under both undirected and directed communication graphs. Then based on the observer and by adding a power integrator, a novel nonlinear protocol is designed such that the estimated leader state is tracked in a prescribed finite-time. Different from some existing finite-time consensus tracking approaches, an explicit bound without dependence on initial states is derived for the settling time. Therefore, in an unknown environment where initial conditions are unavailable, the proposed strategy is able to meet specific system requirements, e.g., a military target is tracked by a group of field robots in a prescribed time. Finally, numerical examples are provided to demonstrate the effectiveness of the proposed protocol.